The organization of the wall filaments and characterization of the matrix structures of Toxoplasma gondii cyst form - Lemgruber, Leandro; Lupetti, Pietro; Martins-Duarte, Erica S.; De Souza, Wanderley; Vommaro, Rossiane C. (Cellular microbiology, 2011)
The encystation process is a key step in Toxoplasma gondii life cycle, allowing the parasite to escape from the host immune system and the transmission among the hosts. A detailed characterization of the formation and structure of the cyst stage is essential for a better knowledge of toxoplasmosis. Here we isolated cysts from mice brains and analysed the cyst wall structure and cyst matrix organization using different electron microscopy techniques. Images obtained showed that the cyst wall presented a filamentous aspect, with circular openings on its surface. The filaments were organized in two layers: a compact one, facing the exterior of the whole cyst and a more loosen one, facing the matrix. Within the cyst wall, we observed tubules and a large number of vesicles. The cyst matrix presented vesicles of different sizes and tubules, which were organized in a network connecting the bradyzoites to each other and to the cyst wall. Large vesicles, with a granular material in their lumen of glycidic nature were observed. Similar vesicles were also found associated with the posterior pole of the bradyzoites and in proximity to the cyst wall.
Gesehen am 15.08.2022